Pengelolaan Penginapan “Family Ngebel” dalam Perspektif Etika Bisnis Islam - Kusnul Ana Solikah; Iza Hanifuddin (Institut Agama Islam Negeri Ponorogo, 2022)
This study aims to determine the implementation of management, attitudes and steps of the owner in managing sharia-based lodging and the implications of the owner's philosophy and efforts with sharia principles on the development of Family Lodging. This research method uses a qualitative descriptive approach. This type of research is field research. This study shows that the management of the family accommodation has been going well and under the values ​​contained in Islamic law. They start by planning, organizing, implementing and monitoring. In the implementation, the manager provides friendly service and a polite appearance. In terms of organization, the manager has a simple organizational structure. In addition, the manager also supervises by evaluating employees. The steps taken by the owner in managing lodging with sharia principles are shown by not providing access to pornography and immoral acts, providing adequate equipment and facilities for worship, designing rooms with three, two, and one lousy cover and without ornaments that lead to polytheism. The implications of applying sharia-based management attitudes and steps to the development of Family Lodging include that the number of consumers has increased significantly from year to year. They are evidenced by the presence of guests who become regular customers.